The clinical efficacy of laboratory risk indicator for necrotizing fascitis score in early diagnosis of patients with necrotizing fascitis - Chowdary, Murakonda Sowmya; D., Srinivasan; N., Sreeramulu P.; Pawar, Tejaswini M.; K., Krishna Prasad (International Surgery Journal, 2021)
Background: Necrotizing fasciitis is a rare, rapidly progressive infection which causes extensive necrosis of the fascia and subcutaneous tissue. Early recognition and debridement are major prognostic determinants, and delay has been shown to increase mortality rate. We describe a novel, simple, and objective scoring system, the laboratory risk indicator for necrotizing fasciitis (LRINEC) score, based on routine laboratory investigations readily available at most centres, that can help to distinguish necrotizing fasciitis (nec fasc) from severe cellulitis or abscess. Methods: We performed a single centre, retrospective, all patients treated at the RLJ Hospital for necrotizing fasciitis between January 2017 and December 2019 were included in this study. The outcome of the study was based on comparing LRINEC score and Wang and Wong staging, which is useful to detect necrotizing fasciitis severity. Results: In our study, males were predominantly affected more common in lower limbs followed by perineum and abdominal wall in their fifties with diabetes mellitus and hypertension as dominant co-morbid diseases. In the study among subjects with high risk score, 83.3% required ICU stay, among subjects with moderate risk, 16.7% required ICU stay and among subjects with low risk, 12.5% required ICU stay. Conclusions: All patients with higher LRINEC scores and who were classified as ‘high risk’ in Wang and Wong classification required ICU stay and significant association with mortality rate.